EPIZOOTOLOGICAL MONITORING OF EIMERIOSIS IN YOUNG CATTLE IN AGRICULTURAL FARMS OF IVANOVO REGION AND CONTIGUOUS AREAS - E. S. Andrushko; S. V. Egorov (Российский паразитологический журнал, 2016)
The infection of cattle with Eimeria spp. In agricultural farms of Ivanovo region was studied. Diagnosis for eimeriosis was made based on epizootological data, clinical signs manifested in calves and results of laboratory examination of fecal samples. Totally 2283 fecal samples from young cattle of various breeds were examined. Cattle feces were investigated by Fuelleborn’s method or centrifuge-flotation technique. The Eimeria species were detected using Krylov indicator (1996). The seasonal and age-related dynamics of calve eimeriosis were studied. An unfavorable situation with regard to eimeriosis has been registered in 8 administrative regions. Eimeriosis was found in 14 of 38 investigated agricultural farms. The extensity of infection of young cattle in the region ranged from 13 to 95 %. The intensity of infection was 1–193 examples of oocysts per microscopic field. It was determined that three species: Eimeria zuerni, E. bovis, E. ellipsoidalis parasitize on young cattle. The extensity of Eimeria spp. Infection was as follows: in cattle at an age of 1 to 2 months – 31 %, 2 to 3 months – 88 %, in young cattle: 3 to 4 months – 63, 4–5 months – 43, 5–6 months – 27 %. Calves are infected with eimeriosis mostly in autumn and spring. In winter the extensity of infection is 23 %, spring – 47, summer – 10, autumn – 39 %.